2015
DOI: 10.1038/srep08602
|View full text |Cite
|
Sign up to set email alerts
|

An efficient process for wastewater treatment to mitigate free nitrous acid generation and its inhibition on biological phosphorus removal

Abstract: Free nitrous acid (FNA), which is the protonated form of nitrite and inevitably produced during biological nitrogen removal, has been demonstrated to strongly inhibit the activity of polyphosphate accumulating organisms (PAOs). Herein we reported an efficient process for wastewater treatment, i.e., the oxic/anoxic/oxic/extended-idle process to mitigate the generation of FNA and its inhibition on PAOs. The results showed that this new process enriched more PAOs which thereby achieved higher phosphorus removal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Thus TN removal performance would be improved if we inserted anoxic phases into the aerobic phase, which has been verified by our recent parallel researches [3]. In addition, previous studies have verified that when receiving the same level of nitrate, the transformations of metabolic intermediates in the AEI regime are much lower influenced than those in the A/O regime [17], indicating that the AEI regime could tolerate a higher level of negative impact caused by nitrogen removal.…”
Section: Substratementioning
confidence: 57%
See 2 more Smart Citations
“…Thus TN removal performance would be improved if we inserted anoxic phases into the aerobic phase, which has been verified by our recent parallel researches [3]. In addition, previous studies have verified that when receiving the same level of nitrate, the transformations of metabolic intermediates in the AEI regime are much lower influenced than those in the A/O regime [17], indicating that the AEI regime could tolerate a higher level of negative impact caused by nitrogen removal.…”
Section: Substratementioning
confidence: 57%
“…In addition, previous studies have verified that when receiving the same level of nitrate, the transformations of metabolic intermediates in the AEI regime are much lower influenced than those in the A/O regime [17], indicating that the AEI regime could tolerate a higher level of negative impact caused by nitrogen removal. Despite only highway rest area domestic sewage being tested in this study, our previous researches have demonstrated that excellent P removal can be achieved in the AEI regime using either synthetic or real common sewage [3,16,17,19,39]. Accordingly, the AEI regime might serve as a scientific basis for developing a new efficient solution to the "nitrogen-phosphorus challenge" faced by WWTPs.…”
Section: Substratementioning
confidence: 91%
See 1 more Smart Citation
“…Meanwhile, as a byproduct of wastewater treatment, waste activated sludge (WAS) is generated in huge quantities daily (Ni and Yu, 2008;Zhao et al, 2015). WAS contains high levels of organic matter, which makes it a plentiful inexpensive source for SCFA production (Yuan et al, 2006;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…15 Further research conrmed that the enrichment mode and metabolic pathway of PAOs in the O/EI regime were signicant different from those in the traditional A/O process (e.g., a signicant idle release of phosphate and a low idle production of PHA). 16,17 Therefore, the new EBPR technology has broad application prospects.…”
Section: Introductionmentioning
confidence: 99%